Emergency Obstetrics Hysterectomy: Current Situation in a Tertiary care Hospital of Sindh - Farkhunda Khursheed, Sabrina Abbas, Chandra Madhudas, Zakia Zaheen, Nargis Bano, Rashida Akbar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the indications of emergency obstetrics hysterectomy (EOH) as a current situation in a tertiary care Hospital of Sindh. Material and Methods: This descriptive cross-sectional study was conducted at obstetrics and Gynaecology department of Liaquat University of Medical and Health Sciences. The study duration was one year from January 2021 to December 2021. All the women underwent emergency obstetric hysterectomies, aged 18 to 40 years, both multi and primiparous of either residential status or booking status were included. Hysterectomy conducted for bleeding unresponsive to conservative medical and surgical treatment at the time of cesarean section or after birth until 42 days postpartum was characterized as obstetric hysterectomy. Patients were assessed regarding indications of the emergency obstetrics hysterectomies. All the data were collected via self-made study proforma. SPSS version 26 was used for the analysis of data. Results: A total of 20 women were studied to assess the indications of emergency obstetrics hysterectomies. The average age of the women was 31.70+3.80 years and mean gestational age was 36.0+2.58 weeks. Placenta previa + morbidly adherent placenta was the most common indication 8(40.0%) with positive history of previous c-sections, uterine rupture was in 06(30.0%) women and placenta previa type IV was 03(15.0%), followed by fibroid uterus with history previous 3 c-sections was 01(5.0%), incomplete mischarge was 01(5.0%) and uterine atony was 01(5.0%). Indications were statistically insignificant according to residential status (p->0.05), while statistically significant according to booking status and parity (p-<0.05). Conclusion: As per current scenario the placenta previa+ morbidly adherent placenta (MAP) with history of multiple previous C-sections and rupture of the uterus were observed to be the frequently prevalent indications of emergency obstetrics hysterectomy. Women who have had past C-sections should receive comprehensive antenatal care.